Technostress Among University Teachers in Higher Education: A Study Using Multidimensional Person-Environment Misfit Theory - Wang, Xinghua; Li, Bo (Frontiers in Psychology, 2019)
To investigate the phenomenon of technostress among teachers in higher education, a multidimensional person-environment misfit framework of technostress was proposed and validated by 343 teachers from universities in China. The findings indicate that person-organization (P-O) misfit, person-technology (P-T) misfit, and person-people (P-P) misfit largely captured how teachers interact with multiple dimensions of the higher education environment in an imbalanced way that causes technostress. P-O misfit predicted P-T misfit and P-P misfit. Relationships between multidimensional technostress and job performance were investigated. It was found that university requirements related to the use of ICT and the suitability of ICT for teachers’ work were critical factors affecting their job performance. In addition, a comparison was made among teachers from different grade levels and reveals that university management related to ICT use tended to affect teachers of higher-grade levels more than those of lower-grade levels in generating technostress.